2000
DOI: 10.1136/bjo.84.8.837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disagreement between refractive, keratometric, and topographic determination of astigmatic axis on suture removal after penetrating keratoplasty

Abstract: Background/aims-Post-keratoplasty astigmatism can be managed by selective suture removal in the steep axis. Corneal topography, keratometry, and refraction are used to determine the steep axis for suture removal. However, often there is a disagreement between the topographically determined steep axis and sutures to be removed and that determined by keratometry and refraction. The purpose of this study was to evaluate any diVerence in the eVect of suture removal, on visual acuity and astigmatism, in patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
(9 reference statements)
1
13
0
7
Order By: Relevance
“…This study showed that corneal topography performed between 30 and 40 min of suture removal can identify the next set of sutures requiring removal. As has been previously conclusively shown, 7,13 selective suture removal in our study also reduced post-keratoplasty astigmatism and improved visual acuity. The reason for leaving the patient for 30-40 min after suture removal is to allow the cornea to take its new configuration after removal of the tight sutures.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This study showed that corneal topography performed between 30 and 40 min of suture removal can identify the next set of sutures requiring removal. As has been previously conclusively shown, 7,13 selective suture removal in our study also reduced post-keratoplasty astigmatism and improved visual acuity. The reason for leaving the patient for 30-40 min after suture removal is to allow the cornea to take its new configuration after removal of the tight sutures.…”
Section: Discussionsupporting
confidence: 67%
“…Topography enables determination of steep semi-meridians corresponding to tight sutures. 13,14 Burk et al 2 evaluated the removal of multiple sutures at the same visit to control post-keratoplasty astigmatism. They reported an average change of astigmatism of 2-3 D, but this average was associated with a large range (0-12 D).…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Buna rağmen postkeratoplasti astigmatizma bu hastalarda tatmin edici görme rehabilitasyonu elde etmede hala en büyük engeldir. 5 Birçok faktör postkeratoplasti astigmatizmanın tahmin edilemeyen ve değişken doğasına katkıda bulunmaktadır. Bunlar alıcı korneanın biyomekaniğini, donör göz ve alıcı yatağının trepanizasyonunu, sütür tekniğini ve postoperatif tedaviyi içermektedir.…”
Section: Discussionunclassified
“…Bunlar alıcı korneanın biyomekaniğini, donör göz ve alıcı yatağının trepanizasyonunu, sütür tekniğini ve postoperatif tedaviyi içermektedir. 3,5 Literatürde 20 D kadar yüksek astigmatizma vakaları bildirilmiştir. 6,7 Yapılan çeşitli araştırmalarda keratoplasti girişimi sonrası olgularda ortalama 4-6 D astigmatizma bulunmuş; göz-lük ve kontakt lensi tolere edemeyen, refraktif cerrahi girişim gerektiren yüksek astigmatizma insidansı en az %10 olarak saptanmıştır.…”
Section: Discussionunclassified
See 1 more Smart Citation